1997
DOI: 10.1068/p261217
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation: Central and Peripheral Effects

Abstract: Assimilation and contrast have opposite effects: Contrast leads to an increase of perceived differences between neighbouring fields, whereas assimilation leads to a reduction. It is relatively easy to demonstrate these effects, but the precise localisation of these effects in the perceptual system is not yet possible. In an experiment the strength of assimilation effects was modified by adding spatial noise. By varying the localisation in perceived space of the added noise (by presentation of the noise pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 12 publications
2
36
0
Order By: Relevance
“…The present research tested the hypothesis that central mechanisms are involved in both contrast and assimilation, and it was inspired by an observation reported by de Weert and van Kruysbergen (1997). By means of a stereo display, de Weert and van Kruysbergen observed that when some red and green discs are painted on a white target, the latter appears greenish when the green discs are perceived at its same depth and the red discs stratify.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…The present research tested the hypothesis that central mechanisms are involved in both contrast and assimilation, and it was inspired by an observation reported by de Weert and van Kruysbergen (1997). By means of a stereo display, de Weert and van Kruysbergen observed that when some red and green discs are painted on a white target, the latter appears greenish when the green discs are perceived at its same depth and the red discs stratify.…”
Section: Discussionmentioning
confidence: 91%
“…According to the level of the visual process they refer to, researchers have provided three interpretations of this relationship. The first asserts that both the phenomena occur at a peripheral level of the visual system (Helson, 1964;DeValois & DeValois, 1975;Hurvich & Jameson, 1966;1974;Jameson & Hurvich, 1975;Reid & Shapley, 1988); the second attributes their occurrence to more central mechanisms (Musatti, 1931;1953;Festinger, Coren & Rivers, 1970;de Weert and Van Kruysbergen 1997;Kanizsa, 1979), and the third claims that contrast involves central mechanisms whilst assimilation involves peripheral ones (Gilchrist et al, 1999). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations